2017
DOI: 10.1016/j.cherd.2017.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Designing full-scale biodigestion plants for the treatment of vinasse in sugarcane biorefineries: How phase separation and alkalinization impact biogas and electricity production costs?

Abstract: Anaerobic digestion (AD) is the most suitable approach for the management of vinasse in sugarcane distilleries because both environmental adequacy and bioenergy recovery could be achieved through biogas production. Because the literature lacks data on the implementation and operation of full-scale AD plants for enhanced energy recovery from vinasse, this study presents different designs for AD plants applied to vinasse in large-scale distilleries, considering both single-and two-phase schemes and different alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 40 publications
2
29
1
5
Order By: Relevance
“…Despite the high cost of building one more reactor, this process yields more biogas, as reported by FERRAZ JÚNIOR et al (2016) who obtained 25.7% more biogas when comparing to biogas produced by a single-stage system. Lately, FUESS et al, (2017) confirmed previous results simulated for full-scale, and e results confirmed that phase separation is economically feasible when scaling up. In spite of the higher capital and operating costs in such schemes, the estimated biogas and electricity production costs reached equivalent or lower values compared to those of a single-phase.…”
Section: Resumo: O Maior Problema Na Digestão Anaeróbia De Resíduos Dsupporting
confidence: 79%
See 3 more Smart Citations
“…Despite the high cost of building one more reactor, this process yields more biogas, as reported by FERRAZ JÚNIOR et al (2016) who obtained 25.7% more biogas when comparing to biogas produced by a single-stage system. Lately, FUESS et al, (2017) confirmed previous results simulated for full-scale, and e results confirmed that phase separation is economically feasible when scaling up. In spite of the higher capital and operating costs in such schemes, the estimated biogas and electricity production costs reached equivalent or lower values compared to those of a single-phase.…”
Section: Resumo: O Maior Problema Na Digestão Anaeróbia De Resíduos Dsupporting
confidence: 79%
“…Hence, with these characteristics, it is possible to confirm that the cost of the limestone used with a final price of U.S. $ 69m -3 is much lower than the costs reported by TORRES et al (2008) for hydrated lime (Ca (OH) 2 ), which was about U.S.$ 320m -3 . The calcium content reported in the present experiment reassure us about the observations of FUESS et al (2017), who reported that in addition to the economic aspects of dosing NaHCO 3 and NaOH as alkalizing agents for sugarcane vinasse, some environmental implications of the alkalinization process should be considered, in particular regarding to the role of sodium ions (Na + ) in soils ferti-irrigated with biodigested vinasse, because the Na + ions act as highly dispersive agents, when hydrated, by disrupting the stable aggregates of the soil, which may drastically reduce water infiltration due to clogging.…”
Section: Analysis -----------------------------------------------Hydrcontrasting
confidence: 42%
See 2 more Smart Citations
“…Esse custo apresentado na Tabela 8-1 pode ser considerado conservador, pois é consideravelmente superior ao obtido por Fuess et al (2017) que chegou ao valor de R$ 0,13/Nm³ de biogás a partir dos custos de construção de um sistema de biodigestão. Apesar dessa vantagem, calculada com custos anualizados, devem ser estudados os indicadores de viabilidade econômica de cada cenário, cujos resultados são mostrados a seguir.…”
Section: Custo Da Produção De Biogás Combustível E De Biometano a Parunclassified